Anti-angiogenic effects of pterogynidine alkaloid isolated from Alchornea glandulosa - Carlos Iracilda Z; Azevedo Isabel; Bolzani Vanderlan S; Silva Dulce HS; Regasini Luis O; Rocha Ana; Pirraco Ana; Lopes Flávia CM; Soares Raquel (BMC, 2009)
Abstract Background Angiogenesis, a complex multistep process that comprehends proliferation, migration and anastomosis of endothelial cells (EC), has a major role in the development of pathologic conditions such as inflammatory diseases, tumor growth and metastasis. Brazilian flora, the most diverse in the world, is an interesting spot to prospect for new chemical leads, being an important source of new anticancer drugs. Plant-derived alkaloids have traditionally been of interest due to their pronounced physiological activities. We investigated the anti-angiogenic potential of the naturally occurring guanidine alkaloid pterogynidine (Pt) isolated from the Brazilian plant Alchornea glandulosa. The purpose of this study was to examine which features of the angiogenic process could be disturbed by Pt. Methods Human umbilical vein endothelial cells (HUVEC) were incubated with 8 μM Pt and cell viability, proliferation, apoptosis, invasion and capillary-like structures formation were addressed. Nuclear factor κB (NFκB), a transcription factor implicated in these processes, was also evaluated in HUVEC incubated with Pt. Quantifications were expressed as mean ± SD of five independent experiments and one-way analysis of variance (ANOVA) followed by the Dunnet test was used. Results A significant decrease in proliferation and invasion capacity and an effective increase in apoptosis as assessed by bromodeoxyuridine (BrdU), double-chamber and terminal transferase dUTP nick end labeling (TUNEL) assay, respectively, have been found. Pt also led to a drastic reduction in the number of capillary-like structures formation when HUVEC were cultured on growth factor reduced-Matrigel (GFR-Matrigel) coated plates. In addition, incubation of HUVEC with Pt resulted in reduced NFκB activity. Conclusion These findings emphasize the potential use of Pt against pathological situations where angiogenesis is stimulated as tumor development.